Exploring The Feasibility Of Residential Solar Panel Adoption In Algeria’s Arid And Hot Regions: A Cost-Benefit Analysis Of An On-Grid System - Tibermacine, Islam; Zemmouri, Nourredine (Technium Social Sciences Journal, 2023)
This research aims to explore the economic and technical feasibility of residential solar panel adoption in Algeria, specifically in its arid and hot regions. By analyzing the potential for solar energy generation and assessing the economic viability of solar panel systems, this study aims to evaluate the financial impact on energy bill savings and the economic feasibility of solar panel adoption. A case study of a residential building located in the city of Biskra is used as a representation of the potential for solar energy in these specific areas, along with real data of energy consumption over the last five years. A simulation of an on-grid system using Skelion plugin and PVsyst software was performed to evaluate the financial impact on energy bill savings. The study also evaluated the economic feasibility through the calculation of costs and benefits, including the payback period, net present value (NPV), and the internal rate of return (IRR). Results showed that solar energy has great potential in Algeria and that residential solar panel systems can provide a positive net present value and internal rate of return, indicating that they are economically viable. Additionally, the payback period for these systems was found to be reasonable. Homeowners who install solar panels on their roof can reduce their dependence on the traditional electricity grid by generating their own electricity, which can lead to significant savings on energy bills and reduce their carbon footprint.